2007
DOI: 10.1111/j.1538-7836.2007.02735.x
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of plasminogen activator inhibitor‐2 impairs nutritionally induced murine adipose tissue development

Abstract: Summary. Background: A functional role for several components of the fibrinolytic (plasminogen/plasmin) system in development of adipose tissue has been demonstrated. No information is available, however, on a potential role of plasminogen activator inhibitor-2 (PAI-2) in obesity. Methods: In vitro, 3T3-F442A murine pre-adipocytes were differentiated into mature adipocytes. In vivo, 5-week-old male PAI-2-deficient (PAI-2 )/) ) mice and wild-type (WT) controls of the same genetic background (C57Bl/6) were kept … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
15
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 36 publications
3
15
0
2
Order By: Relevance
“…Of note, the increased expression of the precursor Tachykinin 1 (Tac1) suggests enhanced production of substance P, which has been reported to promote proliferation of preadipocytes ( 38 ). Regarding adipocyte hypertrophy, the overexpression of PAI-2 (Serpinb2) over generations is consistent with the fact that PAI-2 Ϫ / Ϫ mice fed a high-fat diet exhibit a lower adipocyte size and higher adipocyte number than wild-type mice ( 39 ), and suggests that PAI-2 overexpression promotes excessive WAT development. Reports have implicated Wnt signaling pathway components as proteins that maintain the preadipocyte compartment and inhibit adipogenesis.…”
Section: Genes Regulated By Regimensupporting
confidence: 60%
“…Of note, the increased expression of the precursor Tachykinin 1 (Tac1) suggests enhanced production of substance P, which has been reported to promote proliferation of preadipocytes ( 38 ). Regarding adipocyte hypertrophy, the overexpression of PAI-2 (Serpinb2) over generations is consistent with the fact that PAI-2 Ϫ / Ϫ mice fed a high-fat diet exhibit a lower adipocyte size and higher adipocyte number than wild-type mice ( 39 ), and suggests that PAI-2 overexpression promotes excessive WAT development. Reports have implicated Wnt signaling pathway components as proteins that maintain the preadipocyte compartment and inhibit adipogenesis.…”
Section: Genes Regulated By Regimensupporting
confidence: 60%
“…007234, http://jaxmice.jax.org/strain/007234.html; Jackson Laboratory) has been deposited at Jackson Laboratory and has been distributed to other investigators. All subsequent studies and reports from other groups (14,15,(40)(41)(42) were confined to the 10G3 line. All animal care and experimental procedures complied with the Principles of Laboratory and Animal Care established by the National Society for Medical Research and were approved by the University of Michigan Committee on Use and Care of Animals.…”
Section: Methodsmentioning
confidence: 99%
“…Only two phenotypes have so far been reported for SerpinB2 2/2 mice: increased susceptibility to multistage skin carcinogenesis (31) and increased adipocyte hypotrophy after a high-fat diet (9). Neither phenotype provides discernable insights into the clinical observations.…”
mentioning
confidence: 98%
“…The majority of the .860 publications listed in PubMed on SerpinB2/PAI-2 have thus assumed that the principle role of this serpin is inhibition of uPA, although a number of reports have indicated that certain activities associated with SerpinB2 expression appear unrelated to uPA inhibition (2,6,9,(11)(12)(13)(14). Although SerpinB2 can inhibit uPA in vitro, the evidence that this represents a physiological function for SerpinB2 in vivo is not compelling.…”
mentioning
confidence: 99%
See 1 more Smart Citation